CD100 Effects in Macrophages and Its Roles in Atherosclerosis - Luque, Maria C. A.; Galuppo, Mariana K.; Capelli-Peixoto, Janaina; Stolf, Beatriz S. (Frontiers in Cardiovascular Medicine, 2018)
CD100 or Sema4D is a protein from the semaphorin family with important roles in the vascular, nervous and immune systems. It may be found as a membrane bound dimer or as a soluble molecule originated by proteolytic cleavage. Produced by the majority of hematopoietic cells including B and T lymphocytes, natural killer and myeloid cells, as well as endothelial cells, CD100 exerts its actions by binding to different receptors depending on the cell type and on the organism. Cell-to-cell adhesion, angiogenesis, phagocytosis, T cell priming, and antibody production are examples of the many functions of this molecule. Of note, high CD100 serum levels has been found in inflammatory as well as in infectious diseases, but the roles of the protein in the pathogenesis of these diseases has still to be clarified. Macrophages are highly heterogeneous cells present in almost all tissues, which may change their functions in response to microenvironmental conditions. They are key players in the innate and adaptive immune responses and have decisive roles in sterile conditions but also in several diseases such as atherosclerosis, autoimmunity, tumorigenesis, and antitumor responses, among others. Although it is known that macrophages express CD100 and its receptors, few studies have focused on the role of this semaphorin in this cell type or in macrophage-associated diseases. The aim of this review is to critically revise the available data about CD100 and atherosclerosis, with special emphasis on its roles in macrophages and monocytes. We will also describe the few available data on treatments with anti-CD100 antibodies in different diseases. We hope that this review stimulates future studies on the effects of such an important molecule in a cell type with decisive roles in inflammatory diseases such as atherosclerosis.